Analysis Of The Result Of DNA (Deoxyribonucleic Acid) Electrophoresis On Vaginal Mucosal Swabs With Cervical Cancer Patients - Siti Ramadhani; Vincentia Ade Rizky; Sa'adah Siregar (Institut Kesehatan Medistra Lubuk Pakam, 2024)
Background: Cervical cancer is one of the second-highest sexually transmitted diseases in the world, accounting for 13% of the total 22% of deaths caused by non-communicable diseases. Today there have been many developments about cervical cancer diagnosis methods especially in early detection aimed at recognizing cervical cancer at an earlier stage, including molecular biology detection using PCR tools and electrophoresis. Objective: To identify the results of DNA electrophoresis in vaginal mucosal swabs with cervical cancer. Method : The research method used is experimental. Results: Based on the results of a study using a documentary gel, 2 samples of HPV DNA tape were detected, it was tested positive because there was 450 bp DNA tape and 4 samples of negative results were obtained. Conclusion: The frequency distribution of respondents from 6 samples by using electrophoresis and focumerary gel as readers detected 2 positive samples. A positive result is expressed if a result in the documentary gel is found to be a DNA band. The size of the DNA ribbon produced with the DNA marker markers is at 450 bp, according to the sample target. This shows that the DNA bands in the sample are about 450 bp in size.